Magnetic response of FeRh to static and dynamic disorder. Issue 24 (7th April 2020) - Eggert, Benedikt; Schmeink, Alexander; Lill, Johanna; Liedke, Maciej Oskar; Kentsch, Ulrich; Butterling, Maik; Wagner, Andreas; Pascarelli, Sakura; Potzger, Kay; Lindner, Jürgen; Thomson, Thomas; Fassbender, Jürgen; et al.
Abstract : This study shows the similarity of the thermally-driven (dynamic disorder) and structural disorder-driven (static disorder) magnetic phase transition in B2-FeRh. Abstract : Atomic scale defects generated using focused ion as well as laser beams can activate ferromagnetism in initially non-ferromagnetic B2 ordered alloy thin film templates. Such defects can be induced locally, confining the ferromagnetic objects within well-defined nanoscale regions. The characterization of these atomic scale defects is challenging, and the mechanism for the emergence of ferromagnetism due to sensitive lattice disordering is unclear. Here we directly probe a variety of microscopic defects in systematically disordered B2 FeRh thin films that are initially antiferromagnetic and undergo a thermally-driven isostructural phase transition to a volatile ferromagnetic state. We show that the presence of static disorder i.e., the slight deviations of atoms from their equilibrium sites is sufficient to induce a non-volatile ferromagnetic state at room temperature. A static mean square relative displacement of 9 × 10 −4 Å −2 is associated with the occurrence of non-volatile ferromagnetism and replicates a snapshot of the dynamic disorder observed in the thermally-driven ferromagnetic state. The equivalence of static and dynamic disorder with respect to the ferromagnetic behavior can provide insights into the emergence of ferromagnetic coupling as well as achieving tunable magnetic properties through defect manipulations in alloys.